2016
DOI: 10.1186/s12863-016-0375-4
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between mitochondrial DNA haplotype and the reproductive capacity of domestic pigs (Sus scrofa domesticus)

Abstract: BackgroundThe maternally inherited mitochondrial genome encodes key proteins of the electron transfer chain, which produces the vast majority of cellular ATP. Mitochondrial DNA (mtDNA) present in the mature oocyte acts as a template for all mtDNA that is replicated during development to meet the specific energy requirements of each tissue. Individuals that share a maternal lineage cluster into groupings known as mtDNA haplotypes. MtDNA haplotypes confer advantages and disadvantages to an organism and this affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 64 publications
0
58
0
3
Order By: Relevance
“…10 Animal studies have shown that common haplogroup polymorphisms have consequences for reproductive fitness. 35 In this study, we have found that the inheritance of nuclear and mtDNA from distinct ancestral origins is associated with an increased risk for preterm birth. This finding adds to a growing understanding of genetic influences on gestational duration, 36 a common and serious issue whose complete causes remain unknown.…”
Section: Discussionmentioning
confidence: 67%
“…10 Animal studies have shown that common haplogroup polymorphisms have consequences for reproductive fitness. 35 In this study, we have found that the inheritance of nuclear and mtDNA from distinct ancestral origins is associated with an increased risk for preterm birth. This finding adds to a growing understanding of genetic influences on gestational duration, 36 a common and serious issue whose complete causes remain unknown.…”
Section: Discussionmentioning
confidence: 67%
“…Various mtDNA haplotypes have developed during millions of years of evolution. Previous studies have shown that the polymorphisms in mtDNA were associated with many different phenotypes, such as human disease and animal productive traits [6,8,10]. By generating cybrids, in which the mitochondria from one cell line are transferred into a ρ 0 cell line, direct evidence can be The expression levels of OPA1, MFN1, and MFN2 were used to measure the mitochondrial fusion ( Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…For animals, mtDNA haplotypes have been reported to associate with economically important traits, such as the milk quality of Holstein cows and reproductive capacity of pigs [7,8]. Many studies also indicate that mtDNA polymorphisms are correlated with growth traits, such as pectoral muscle fat content, duodenum length, Marek's disease resistance, and hypoxia adaptation in chicken breeds [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Then, we inferred previously unknown matrilineage for T24, T47, and T104 using the same approach. We expect a single mutation between individuals to arise spontaneously (Baltazar‐Soares & Eizaguirre, 2016; Tsai, Rajasekar, & John, 2016) and hence ignore a single mutational distance for the scope of this study.…”
Section: Methodsmentioning
confidence: 99%